Consumption of dietary supplements by exercise practitioners (Research, Society and Development, 2021)
The objective was to verify the profile of the main consumers of dietary supplements, the main supplements consumed and the practice of physical exercises associated with consumption, as well as the main professionals who indicate supplementation. In order to carry out this study, scientific articles were searched in national and international journals and journals that dealt with the proposed theme. After conducting the review on the subject, it can be concluded that most people consume food supplements without the indication of a trained professional, and concomitant to this fact, it can trigger serious health problems. You can see that both sexes consume food supplements for similar purposes.